1545 metų Livonijos ir Lietuvos Didžiosios Kunigaikštystės sienos patikrinimas (Livonijos pareigūnų ataskaita) - Čelkis, Tomas; Antanavičius, Darius (Lietuvos istorijos studijos, 2011)
This is the publication of 1545, the borderline audit between Livonia and the Great Duchy of Lithuania (GDL) reported by the Livonian officers. Such verification documents containing an explicit borderline description are infrequent. Unilateral line reviews are usual in sovereign office correspondence with a neighbor state, informing the latter about the practice that had been undertaken. Border marks, such as stones with incused Livonian crosses or the GDL blazon horseman Vytis confer to the publication of this document an exceptional value in Livonia and GDL borderline studies. Specifically, iconographic information and the depicted border mark "sculpture" are particularly important to the researchers. The document contains facts about the border marks deranged by the GDL inhabitants (it was common to blame them on damaging the other side), but more important is the fact that the ways of damaging are also mentioned; for instance, marks made on trees were burnt. Such records are especially rare. The document contains toponymic and geographical information as well: the mound names by the borderline and even the temple on one of the mounds are mentioned. With all this in mind, the publication becomes a great asset in historical geography and cartography studies.